INHIBITION OF THE HEDGEHOG PATHWAY TARGETS THE TUMOR-ASSOCIATED STROMA IN PANCREATIC CANCER - Hwang, Rosa F. (2012)
The Hedgehog (Hh) pathway has emerged as an important pathway in multiple tumor types and is thought to be dependent on a paracrine signaling mechanism. The purpose of this study was to determine the role of pancreatic cancer-associated fibroblasts (human pancreatic stellate cells, HPSCs) in Hh signaling. In addition, we evaluated the efficacy of a novel Hh antagonist, AZD8542, on tumor progression with an emphasis on the role of the stroma compartment. Expression of Hh pathway members and activation of the Hh pathway were analyzed in both HPSCs and pancreatic cancer cells. We tested the effects of SMO inhibition with AZD8542 on tumor growth in vivo using an orthotopic model of pancreatic cancer containing varying amounts of stroma. HPSCs expressed high levels of SMO receptor and low levels of Hh ligands, whereas cancer cells showed the converse expression pattern. HPSC proliferation was stimulated by sonic Hedgehog with upregulation of downstream GLI1 mRNA. These effects were abrogated by AZD8542 treatment. In an orthotopic model of pancreatic cancer, AZD8542 inhibited tumor growth only when HPSCs were present, implicating a paracrine signaling mechanism dependent on stroma. Further evidence of paracrine signaling of the Hh pathway in prostate and colon cancer models is provided, demonstrating the broader applicability of our findings. CONCLUSION: Based on the use of our novel human derived pancreatic cancer stellate cells, our results suggest that Hh-targeted therapies primarily affect the tumor-associated stroma, rather than the epithelial compartment.